What the Photoreseptor Outer Segment Length Tells Us - Gamze Karatas (Highlights on Medicine and Medical Research Vol. 13, 2021)
Recent advances in ocular imaging technology have successfully introduced novel analyses of retina morphology. It is the most common tool we use to show the Spectral domain optic coherence tomography retinal layers. There are four hyperreflective outer retinal lines on SD-OCT: external limiting membrane (ELM), inner segment ellipsoid (ISel, previously called the junction between the inner and the outer segments (IS/OS junction)), cone outer segment tips (COST), and retinal pigment epithelium (RPE). The PROS is located in between IS/OS and RPE. While measuring the PROS length, we only take measurements from the fovea where the cone cells are located. These cells are directly related to visual acuity and quality. In a database study on this subject ‘The difference in PROS length was not statistically significant neither for age nor for gender; females tended to have a lower PROS length than males and PROS length was slightly higher in the first two decades of life’ the data has been revealed. Also similar studies have been conducted for many diseases. We know that a retinal structure (PROS length) that gives so much information about vision and vision quality will be used more frequently in our daily practice in the future.